IMPLEMENTASI PROGRAM BERAS MISKIN (RASKIN) UNTUK MASYARAKAT MISKIN DI KELURAHAN KOTA LAMA KECAMATAN KUNTO DARUSSALAM - Rahmat Swandi. S; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Poor Rice Program (Raskin) is a program of assistance in the form of subsidized rice to poor households in order to reduce the burden of household expenditure in meeting the basic needs of life. Village of Kota Lama is one of the villages receiver Poor Rice Program (Raskin) which still found the poor families who have not got a poor rice. Other Fenomena, data collection process Target Households (RTS) recipients Raskin who are not current or Central Statistics Agency (BPS) invalid without coordinating with the village government, Price redeem Raskin (HTR) paid by Household Target-Beneficiaries (RTS-PM) Raskin above the normative price (Rp. 2,500 / kg) and a delay in Raskin distribution.In this study the theoretical concept used is based upon the theory of policy implementation put forward by Tangkilisa which explains that the implementation is a series of activities after a policy is formulated. Implementation of Poor Rice Program (Raskin) at the village in its Implementation activities include the establishment Capping Raskin / Allocation Raskin, renewal List of Beneficiaries (DPM) Raskin, Raskin distribution from the distribution point to point to or to Target Households Beneficiaries (RTS-PM), and payment Price Translucent Raskin (HTR).Research results of Poor Rice Program (Raskin) in the village of Kota Lama indicate that the maximum benefits of Raskin has not felt by Household Target-Beneficiaries (RTS-PM) Raskin or poor people, where there are poor people who have not received rice for the poor, Price redeem Raskin (HTR) paid by RTS-PM Raskin above the normative price (at Rp. 2,500 / kg) as well as a delay in the implementation of the distribution / distribution Raskin to RTS -PM.Key word: Poor Rice Program, Capping Raskin, Target Households (RTS), the Poor People.